(Re)branding the ‘other’: an analysis of female characters’ namings in Dina Zaman’s short stories / Nazima Versay Kudus - Kudus, Nazima Versay (Universiti Teknologi MARA, Pulau Pinang & Pusat Penerbitan Universiti (UPENA), 2013)
The objective of this paper is to study how the aspects of naming, i.e., direct naming and nicknames of the Malay women characters in Dina Zaman’s selected short stories are constructed and/or contested, thus illuminating that names are not arbitrary, but are consciously chosen and important in the story-telling process. The corpus for this study is selected from Zaman’s anthology of short stories, Night & Day. The chosen short stories are “The Kacang Puteh and Assam Lady”, “Ani” and “The Fat Woman”. These stories were chosen because they deal specifically with Malay women characters. Meanings related to English language will be sought in the Oxford Advanced Learners Dictionary (hereinafter OED) while the Malay language in Kamus Dewan. Such choices of namings employed by Zaman show that the author does not subscribe to the stereotypical namings of the protagonists, which simultaneously suggest her non-judgmental attitude towards the characters. Thus, as an author, Zaman has challenged the stereotypical naming assigned to these characters.